The Phenolic Compounds Isolated from Myristica fragrans and Their Cytotoxic Effects on B16-F10 Melanoma Cancer Cell Lines - Hasbilla, Raihan Fathurrahman; Riyadi, Sandra Amalia; Safriansyah, Wahyu; Hidayat, Ace Tatang; Susianti, Susianti; Salam, Supriyanto; Lesmana, Ronny; Retnowati, Rurini; Supratman, Unang (Universitas Jenderal Soedirman, 2025)
Phenolic compounds are a major type of secondary metabolite found in plants. These compounds are synthesized through shikimic and phenylpropanoid pathways, resulting in the formation of numerous unique structures and bioactivities. In addition, a significant amount has been reported in nutmeg, an endemic plant of Indonesia, which has been widely used in traditional medicine. A previous study also revealed that ethyl acetate extract of the plant has notable cytotoxic effects against melanoma B16-F10. Therefore, the purpose of this study is to isolate and evaluate phenolic compounds in nutmeg for their potential to inhibit B16-F10 melanoma cancer cell growth. The seeds extract of nutmeg was separated by various chromatographic techniques to yield a total of five compounds, which were identified through spectroscopic analysis (HR-TOF-ESI-MS, IR, and NMR) as well as comparison with literature. The compounds 1-5 were identified as (+)-veraguensin (1), 3',4',5'-trimethoxycinnamyl alcohol (2), (+)-galbegin (3), (-)-polysphorin (4), and 7-methoxycoumarin (5). Cytotoxic effects were then assayed against B16-F10 melanoma cell lines using the Resazurin method. Furthermore, compound 1 displayed the highest cytotoxic activity, with an IC50 value of 112.71 µM.